Proportion of parental genomes in hybrids Allium cepa × A. roylei determines which one becomes dominant - David Kopecký; Martin Duchoslav; Olga Scholten; Jana Kneřová; Marek Szecówka (The Plant Genome)
Abstract Interspecific hybridization leads to complex interactions between the parental genomes, often in the form of genome dominance, where one genome prevails over the other. This phenomenon has been attributed to differential chromosome behavior during meiotic division and may involve either female or male meiosis, or both. In hybrids of Allium cepa × A. roylei, only female meiosis is involved, favoring the transmission of A. roylei chromosomes; male meiosis leads to the development of gametes with equal proportion of parental genomes. Female meiotic drive shifts the genome composition from 8R (A. roylei) + 8C (A. cepa) chromosomes in F1 to 9.3R + 6.7C in F2. In this study of two successive backcross generations with A. cepa (BC1 [first backcross generation] and BC1F1 [progeny after intercross of the first backcross generation]), we observed a change in genome dominance: the A. roylei genome, initially dominant during the meiosis in the F1 hybrids, became submissive in BC1, resulting in a genome composition skewed toward A. cepa. Among 23 BC1 and 236 BC1F1 plants, we observed a significant deviating trend of gradual reduction in A. roylei chromosome representation. The reduction was higher in the lineages with more unequal starting proportion of the parental genomes. This study highlights the dynamic nature of genomic interactions in hybrids and raises questions about the underlying molecular mechanisms driving these changes in dominance, as well as the potential for manipulating these interactions for agricultural benefit. Further exploration of the chromosomal behavior during meiosis across various hybrids will deepen our understanding of non‐Mendelian inheritance patterns and their implications in plant breeding.